Factors Affecting Flemish, Lithuanian and Latvian Foster Parents' Perception of Problem Behaviour and Support Needs. - De Coster, Matthias; Vanderfaeillie, Johan; West, Delphine; Verheyden, Camille; Pigozne, Tamara; Pivorienė, Jolanta; Van Holen, Frank (Child & Family Social Work, 2026)
Emotional and behavioural problems are common among children in foster care. Foster parents usually are the first to notice problematic behaviour and to estimate support needs. They consider themselves experts for that matter. However, it is unknown what impacts the decisions they make in that regard. A total of 443 Flemish, Lithuanian and Latvian foster parents participated in a study set up to examine how foster parents perceive problem behaviour and extra support needs in foster children and their foster parents. The case factors gender of the foster child, type of problem behaviour and parenting quality; the decision‐maker factors control and number of foster children; and the external factor nationality were of overall influence. Other factors' impact was more spread. Foster parents' judgement on the presence of emotional and behavioural problems and their subsequent decision on a course of action for foster children proves them to be consistent. The indirect impact a foster care system that knows interventions aimed partially or entirely at dealing with problem behaviour had on all three decisions points out the importance of supporting foster parents.